Constitutive Expression of Candida antarctica Lipase B (CALB) in Pichia pastoris Using pGAPZÎ± Vector - Wahyuni, Febriana Dwi; Fuad, Asrul Muhamad; Suharsono, Suharsono (ANNALES BOGORIENSES, 2016)
The CalBsyn gene was previously constructed synthetically to encode Candida antarctica lipase B (CALB). Lipase from CalBsyn gene is slightly different from that of wild type CALB (CALB-wt) where it has three amino acids substitutions at different positions, i.e. V210I, A281E, and V221D, to improve enzymeâs thermostability and catalytic efficiency. The CalBsyn gene was isolated from pJ912-CalBsyn vector by digestion using XhoI restriction enzyme. The CalBsyn gene then was ligated to pGAPZÎ± expression vector and transformed into E. coli TOP10Fâ in order to obtain recombinant vector pGAPZÎ±-CalBsyn. The result showed that pGAPZÎ±-CalBsyn recombinant vector was successfully transformed into E. coli TOP10Fâ with transformation efficiency of 4.11 x 103 cfu/Âµg plasmid DNA. The pGAPZÎ±-CalBsyn recombinant plasmid was successfully introduced into Pichia pastoris SMD1168H using electroporation method with transformation efficiency of 1.01 x 102 cfu/Âµg DNA. Qualitative lipase activity assays showed that transformed P. pastoris secreted recombinant lipase (CALB) and has lipolytic activity; while quantitative lipase activity assays showed that the lipase activity was 63.5 Units/ml in 48 hours. Analysis using SDS-PAGE showed that CALB protein was expressed successfully and the recombinant proteinâs molecular size was approximately 45 kDa.